2014
DOI: 10.1021/jp412180t
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport and Separation Dynamics at the C60/GaAs(001) Interface

Abstract: We probe charge separation dynamics at a model hybrid organic/ inorganic semiconductor heterojunction, C 60 /GaAs(001), using time-resolved twophoton photoemission spectroscopy (TR-2PPE). For a p-type GaAs(001) surface with downward band bending, TR-2PPE allows us to directly follow the subpicosecond drift of photoexcited electrons toward the surface by the space charge field. Upon C 60 adsorption, we find that electron transfer from the GaAs conduction band to C 60 occurs on the faster time scale of ≤0.1 ps. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Previous ultrafast surface science investigations have shown that the dynamics of an electronic state in a molecular film can differ based on the molecular properties of the film, the electronic state localization, influence of the metal substrate, and molecular film thickness. 8,10,[27][28][29][30][31][32][33][34][35] The contrasting dynamics of electron localization in nonpolar n-heptane versus polar water and ammonia highlight the influence of the molecular properties of the film. In ultra-thin non-polar n-heptane layers on a Ag(111) surface, electron injection leads to the formation of small polarons that are self-trapped via the in-phase methylene rocking of n-heptane on an approximately 360 fs timescale.…”
Section: Introductionmentioning
confidence: 99%
“…Previous ultrafast surface science investigations have shown that the dynamics of an electronic state in a molecular film can differ based on the molecular properties of the film, the electronic state localization, influence of the metal substrate, and molecular film thickness. 8,10,[27][28][29][30][31][32][33][34][35] The contrasting dynamics of electron localization in nonpolar n-heptane versus polar water and ammonia highlight the influence of the molecular properties of the film. In ultra-thin non-polar n-heptane layers on a Ag(111) surface, electron injection leads to the formation of small polarons that are self-trapped via the in-phase methylene rocking of n-heptane on an approximately 360 fs timescale.…”
Section: Introductionmentioning
confidence: 99%
“…One way to utilize the hot carriers for enhancing the efficiency of photo energy conversion is to realize a charge separation at the interfaces by extracting the hot carriers from the photoconverter before they cool, which can also produce an enhanced photovoltage and suppress the electron–hole recombination. , In order to realize this, the interfacial charge transfer across the contacts must be faster than the rate of carrier cooling . Although numerous experimental and theoretical studies have been carried out to investigate the charge separation mechanism at the interface of hybrid solar cells in order to develop high-efficiency photovoltaic or photocatalysis materials, it is still one of the most important and challenging problems in this field.…”
mentioning
confidence: 99%
“…97,98 In such a charge separation process, it is required that the interfacial charge transfer across the contacts must be faster than the rate of carriers cooling. 99 In spite of numerous investigations on the charge separation mechanism at the hybrid solar cell interfaces, 98,[100][101][102][103][104][105][106][107][108][109][110] this is still one of the most important and challenging problems in this field. Using NAMD simulations, Guo et al 111 proposed that the superatom molecular orbitals (SAMOs) and the nearly free electron (NFE) states of carbon nanostructures which were initially discovered by Feng et al, 112 is an ideal media for interfacial charge separation.…”
Section: Superatom Molecular Orbital As An Interfacial Charge Separmentioning
confidence: 99%